1963
DOI: 10.1002/bbpc.19630670115
|View full text |Cite
|
Sign up to set email alerts
|

Das IR‐Spektrum zonengeschmolzenen Naphthalins

Abstract: Viele bisher veröffentlichte IR‐Spektren des Naphthalins enthalten Banden, die von Verunreinigungen herrühren. Bei Naphthalin, das durch mehrfaches Zonenschmelzen gereinigt wurde, konnten diese Banden, von denen die intensivsten 689, 734, 760 und 1421 cm−1 sind, nicht mehr gefunden werden. Damit wird das Problem der vollständigen Zuordnung des Naphthalin‐Schwingungsspektrums wieder aktuell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1964
1964
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Digermane wras also studied in detail (128). Out-of-plane bending CH modes and their use in determining substitution types in polynuclear aromatics were discussed (115), while Mecke et al (381) suggested that the naphthalene assignment should be reconsidered in view' of the absence of several reported bands from the spectrum of their zone refined sample.…”
Section: Vibrational Assignments and Molecular Structure Studiesmentioning
confidence: 99%
“…Digermane wras also studied in detail (128). Out-of-plane bending CH modes and their use in determining substitution types in polynuclear aromatics were discussed (115), while Mecke et al (381) suggested that the naphthalene assignment should be reconsidered in view' of the absence of several reported bands from the spectrum of their zone refined sample.…”
Section: Vibrational Assignments and Molecular Structure Studiesmentioning
confidence: 99%